Cover Feature: Synthesis and Characterization of the Manganese Hydroxide Halides Mn(OH)X (X = Br, I) and Crystal Structure of trans‐MnBr2·4H2O (Z. Anorg. Allg. Chem. 14/2019). Issue 14 (19th July 2019) - Falkowski, Viktoria; Zeugner, Alexander; Isaeva, Anna; Wurst, Klaus; Ruck, Michael; Huppertz, Hubert
Abstract : The cover picture shows the layered manganese hydroxide halides Mn(OH) X ( X = Br, I). The highly hygroscopic compounds were obtained by means of high‐pressure/high‐temperature synthesis using a Walker‐type multi‐anvil press. The structure in the space group P 21 /c is composed of edgesharing distorted mer ‐Mn(OH)3 X 3 octahedra forming corrugated layers. Weak hydrogen bonds interact between adjacent layers. In the field of well‐explored divalent metal hydroxide halides they represent the first crystalline compounds with this composition. More details are discussed in the article by Viktoria Falkowski, Alexander Zeugner, Anna Isaeva, Klaus Wurst, Michael Ruck and Hubert Huppertz on919 .